Pathology of Comparative Humor Studies (1378-1400) - Raziye Jafari; Mohammad Hosein karami Karami (ادبیات تطبیقی, 2022)
1. IntroductionThe scientific articles that are published in the periodicals of any country are among the most important scientific treasures of that country. One of the issues that has attracted the attention of researchers and literary critics is the analysis of humor and the works of humorists, as one of the most important tools for understanding the thoughts and cultures and social and political characteristics of different societies. The literature of every society, with the help of the element of humor, goes against the unfavorable situations of the society, and on its way, it causes changes in different aspects, and this affects such social, political and cultural fields and is mutually affected by them. Therefore, satirical studies provide us with valuable information about various political, social and cultural issues of different societies. On the other hand, with the growth and development of comparative studies, the researchers of different nations have investigated and compared humor and the works of their humorists with different nations and investigated their differences and similarities and the causes and contexts of these similarities and differences as well as their impact on They have shown interest in each other. Today, we see many comparative studies in the field of humor studies. By examining and analyzing the content of comparative humor research articles, this research shows the quantity and quality of these articles, and to what extent they are written based on the scientific principles of comparative studies, and what are their strengths and weaknesses.  MethodologyThis research has analyzed 39 comparative scientific articles in the field of humor research using the content analysis method. First, by using famous Persian websites such as Noormags.ir, Magiran.com, Humanities Comprehensive Portal, Academic Jihad Scientific Database (SID.ir), etc. Either the abstract or the keywords of comparative literature and humor have been used, it was determined, then the articles were reviewed and evaluated according to the criteria approved by comparative literature, and the results were determined on the graph.  Discussion Pathology of comparative satirical essaysIn order to explain the meaning of comparative literature, we should linger more in front of its concept, to remove what the comparative researchers have wrongly put in the category of comparative literature. In this section, the pathology of comparative research in the field of humor has been discussed under the two topics of subject matter and research methodology, and cases such as methodology in research, incomplete understanding of comparative literature and only finding similarities and differences in works, having creativity and innovation, addressing generalizations. And inattention to details, lack of use of reliable scientific sources, ignorance or knowledge of the principles of comparative literature have been examined in researches.  ConclusionA high frequency of articles written in the field of comparative studies, inspired by the word (adaptation), have limited themselves to comparing the similarities and differences of two works and have chosen the title (comparative review) for their articles; Now that comparative literature has important principles that it is international and intercultural and interdisciplinary, examining the influence and influences of cultures and works of literature on each other, important factors and contexts in the influence of one culture on another culture and why and how the similarities and differences are, and also examining The transformative elements are among the most important of these principles. In the list of sources of most of the comparative articles published in the field of humor studies, not even one of the reliable and important sources of the field of comparative studies can be seen, and even in some cases, no comparison has been made regarding the similarities and differences, and throughout the article, only the word comparative is mentioned in the title. The articles written in the field of comparative literature lack structure and scientific content in most cases, the research method is not given, or the term (descriptive analysis based on comparison) is sufficient, and only a handful of articles refer to the American or French school of comparative literature is mentioned. The articles that have the necessary knowledge about comparative literature are those that, while referring to the concept of comparative studies, have introduced their research outside of the comparative field.